2020
DOI: 10.1111/1756-185x.14003
|View full text |Cite
|
Sign up to set email alerts
|

YouTube for information about side effects of biologic therapy: A social media analysis

Abstract: The advent of biologic therapies was one of the most significant breakthroughs in the treatment of rheumatic pathologies, through which many patients who failed to respond to conventional immunosuppressive therapies achieved disease remission. 1,2 Despite the positive results of these new therapies, there is still some uncertainty concerning response variability, long-term patient safety, and management in daily clinical practice. 3 Several studies have been published on biologic therapy safety in rheumatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
4
21
0
2
Order By: Relevance
“…Similarly, in a study evaluating the quality and validity of spondyloarthritis videos, 62% of the videos were uploaded by healthcare professionals [20]. In another study, YouTube videos about the side effects of biological drugs were evaluated, and it was emphasized that 33.8% of the videos were uploaded by professional organizations and physician groups [23]. Similarly, in this study, 56.9% of the anakinra selfinjection videos were uploaded by physicians.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, in a study evaluating the quality and validity of spondyloarthritis videos, 62% of the videos were uploaded by healthcare professionals [20]. In another study, YouTube videos about the side effects of biological drugs were evaluated, and it was emphasized that 33.8% of the videos were uploaded by professional organizations and physician groups [23]. Similarly, in this study, 56.9% of the anakinra selfinjection videos were uploaded by physicians.…”
Section: Discussionmentioning
confidence: 65%
“…Previously, many studies have been conducted to evaluate the quality of open-access videos about health information in different branches. In the study of Zengin et al in which they evaluated the videos on the side effects of biological agents, it was reported that 40.3% of the videos were high quality, 23.4% of intermediate quality and 36.4% of low quality [23]. In another study, 34% of the videos about secukinumab were reported to be of high quality, 32% of intermediate quality, and 34% of low quality [26].…”
Section: Discussionmentioning
confidence: 99%
“…The last two decades have shown the capacity for technological development and the human ability to incorporate it into daily routines [9][10][11]31,32,35]. In the case of the Internet, its birth and evolution have meant a before and after in humanity [12,13,33,34], and has altered the way people communicate and collaborate [1,18]. Having and using a smartphone [21], even becoming addicted [51], or spending time on social networks [2] are new patterns of behavior in a society where digital skills are becoming essential [26,27,29,36,38].…”
Section: Discussionmentioning
confidence: 99%
“…This is an interest that responds to a historical moment in which social networks offer the right possibilities to cover everything from the individual to the social [31], including work [32]. Some of the main characteristics that may justify this phenomenon are: being a quick and easy alternative to access a wide range of information [33,34], offering almost instantaneous interaction and communication [35], opening up business possibilities in global environments and not just local ones [36], and even serving as a parallel strategy to find out preferences and interests in particular issues [37]. These applications accompany the new digital habits, especially among the young, whose interest in the more classic media is declining and who are developing new digital skills in areas such as content consumption [38].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has found that the quality of YouTube videos on various health issues is low. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Cardiac Surgery is complex in nature, and the informed consent process is likewise. Due to COVID-19 related restrictions on access to traditional healthcare, more patients undergoing Cardiac Surgery may be using YouTube for education.…”
mentioning
confidence: 99%